Pengaruh Current Ratio dan Ukuran Perusahaan Terhadap Pertumbuhan Laba Perusahaan Food and Beverage - Reyza Hatipah Puspitasari; Sri Wahyuni Jamal; Fenty Fauziah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research examines the effect of current ratio and company size on profit growth in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the period 2015 to 2023. All companies in this sub-sector are the research population, with sample selection using purposive techniques based on certain criteria. A total of 72 observation data were analyzed using a quantitative approach through multiple linear regression. Data were obtained from the annual financial reports that have been officially published. The results of the analysis show that the current ratio does not have a significant effect on profit growth, indicating that the level of liquidity does not always contribute directly to profitability. On the other hand, company size has a significant effect, indicating that a larger operational scale and the availability of adequate resources have a positive impact on profit performance. These findings are expected to be a reference in making corporate financial decisions and considerations for further research in the field of corporate finance.